Antidepressant effect of taurine in chronic unpredictable mild stress-induced depressive rats - Gao-Feng Wu (Nature Portfolio, 2017)
Abstract Depression, a psychiatric and dysthymic disorder, severely affects the learning, work and life quality. The main pathogenesis of depression is associated with central nervous system (CNS) dysfunction. Taurine has been demonstrated to exert protective effects on the brain development and can improve learning ability and memory. Our study investigated the antidepressant-like effects of taurine pre-treatment by examining the changes in depression-like behavior, hormones, neurotransmitters, inflammatory factors and neurotrophic factors in the hippocampus of a chronic unpredictable mild stress (CUMS)-induced depressive rat model. Taurine was found to inhibit the decrease of sucrose consumption and prevent the deficiency of spatial memory and anxiety in rats exposed to CUMS, suggesting a preventive effect of taurine on depression-like behavior. Furthermore, the decreased levels of 5-hydroxytryptamine, dopamine, noradrenaline; the increased levels of glutamate, corticosterone; and the decreased expressions of fibroblast growth factor-2, vascular endothelial growth factor and brain derived neurotrophic factor in depressive rats were hindered by taurine pre-administration. However, tumor necrosis factor-α and interleukin-1β levels were not significantly changed by taurine. The results demonstrated that the anti-depressive effect of taurine may be involved in the regulation of hypothalamic-pituitary-adrenal (HPA) axis and the promotion of neurogenesis, neuronal survival and growth in the hippocampus.